The Lime Juice Run - Murrell, Di (Petits Propos Culinaires, 2014)
A memoir of life on a working canal boat during the 1970s -- in particular as part of a transport chain servicing L. Rose & Sons, the makers of a brand of lime cordial -- and the problems of provisioning for such work.